(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction: Acetaldehyde (AA) is a main mediator of neurotoxicity among methabolites of ethanol (E). Purpose. To study the correlation between concentration of E and AA in retrobulbar tissue (RBT), vitreous humor, blood and morphometric and cytophotometric data of optic nerve, choroid and retina ganglion cells layer in experimental chronic alcohol intoxication. Material and methods. Experimental investigation was performed in 24 male Chinchilla rabbits including 6 rabbits of the control group. Results. Negative correlation (p<0,05) was established between acetaldehyde (AA) in retrobulbar tissue (RBT) and choroid thickness (Spearman coefficient p= -0,84), thickness of ganglion cells layer of retina (p = -0,80) and diameter of its nuclei (p= — 0,64), diameter of optic nerve fibres (in intrabulbary part p= -0,70, in retrobulbarypartp= -0,76, in intracanalicularpartp= -0,85, in intracranial part p = -0,78). Positive correlation (p<0,05) was observed between AA in RBT and optic density of cytoplasm RNA of choriocapillaries endotheliocytes (p=0,57). Conclusions. Treatment with polyoxidonium intravenously and by endonasal elec-trophoresis after alcohol deprivation contributes to elimination of AA from RBT, which results in improvement of morphofunctional state of optic nerve, choroid and retina.